The impact of COVID-19 lockdown on professional soccer players' body composition and physical fitness. - Parpa, Koulla; Michaelides, Marcos (Biology of Sport, 2021)
During the COVID-19 lockdown, professional soccer players ceased their regular team training sessions and were provided with exercise programs to follow independently. This investigation assessed the impact of a 7-week COVID-19 lockdown and home-based individual physical training on professional soccer players’ body composition and physical fitness. The study consisted of nineteen division 1 elite soccer players (age 27.68 ± 5.99 years, height 178.47 ± 5.44 cm) and compared the anthropometric and physical fitness parameters obtained post-transition period to those obtained post-COVID-19 lockdown. The statistical analysis indicated that body fat percentage was significantly higher after the lockdown period [t(18) = -5.59, p < 0.01, d = 0.56]. Furthermore, VO2max [t(17) = -11.54, p < 0.01, d = 0.57] and running time [t(17) = 3.94, p < 0.01, d = 0.76] values were significantly higher after the COVID-19 lockdown than those obtained after the transition period. In addition, significantly higher level of performance was demonstrated on squat jump [t(18) = -4.10, p < 0.01, d = 0.30], countermovement jump [t(18) = -7.43, p < 0.01, d = 1.11] and sit and reach tests [t(19) = -5.33, p < 0.01, d = 0.32]. Concurrently, lower body strength was indicated to be significantly greater (p < 0.01) following the COVID-19 lockdown. The training protocol provided during the confinement, due to the COVID-19 outbreak, was effective in keeping physical fitness at a significantly higher level compared to the transition period. Coaches and trainers are encouraged to examine the effectiveness of this protocol, as it may help them develop effective periodization programs during the transition period. This protocol may aid in the development of effective periodization programs that require minimal equipment and can be followed in similar situations.